Updating the option implied probability of default methodology - Johannes Vilsmeier (Deutsche Bundesbank, 2014)
In this paper we 'update' the option implied probability of default (option iPoD) approach recently suggested in the literature. First, a numerically more stable objective function for the estimation of the risk neutral density is derived whose integrals can be solved analytically. Second, it is reasoned that the originally proposed approach for the estimation of the PoD produces arbitrary results and hence an alternative procedure is suggested that is based on the Lagrange multipliers. Based on numerical evaluations and an illustrative empirical application we conclude that the framework provides very promising results.
Keywords: C51; C52; C61; G12; G24; G32; 330; Option Implied Probability of Default; Risk Neutral Density; Cross Entropy